Introduced mice influence the large-bodied alpine invertebrate community - Aaron Bertoia; Tara J. Murray; Bruce C. Robertson; Joanne M. Monks (Biological Invasions, 2024)
Invasive mammalian predators are a key threat to native fauna globally. Island ecosystems that developed in isolation from mammals are particularly threatened by introduced mammalian predators. This is the case in New Zealand, where introduced mammalian predators have caused the decline of native birds, lizards, and invertebrates. In alpine areas of New Zealand, predator control targets stoats, rats, and cats as they are recognised as the key threats to native birds. Mice, which are known predators of invertebrates at lower elevations, are not actively controlled. As a result, alpine invertebrates in New Zealand represent an ideal focus for a natural experiment to understand the effects of predator control efforts and invasive mice on native invertebrates that evolved in isolation from mammals. In the Fiordland region of New Zealand, we assessed the large-bodied alpine invertebrate community at eight different sites that vary in their occurrence of mice and control of higher-order predators. We found that the recent presence of mice influenced the invertebrate community: wētā (a group of native orthopterans) were less common at sites where mice were present, and the mean body size of invertebrates collected in pitfall traps was larger at sites where mice were absent compared to sites where they were present. Control of other predators (specifically rats and mustelids) did not influence invertebrate body size, abundance, or community composition. Our findings suggest that, as in lowland environments, mice are an important predator of large-bodied invertebrates in the alpine zone and should be incorporated into future predator management programmes.